PENGARUH MODEL PEMBELAJARAN STAD TERHADAP KEMAMPUAN BERHITUNG PERKALIAN DAN PEMBAGIAN PADA SISWA KELAS V SDN BILAPORAH 1 BANGKALAN - Adinda Putri Septia Ningsih; Nor Aida Amalia Putri; Noura Aulya Damayanti; Indrastuti Ratih Fidila; M Nur Afifudin Dwi Maulana; Ahmad Sudi Pratikno (Jurnal Binagogik, 2025)
The research's background is the low learning outcomes of fifth-grade students and the often teacher-centered teaching methods, especially for mathematics, using the lecture method. Fifth-grade students should master multiplication and division skills at the elementary school level. The purpose of this study was to examine the effect of the STAD learning model on fifth-grade students' multiplication and division skills at SDN Bilaporah 1 Bangkalan. This study employed a quantitative approach using a Quasi-Experimental Non-Randomized Pretest-Posttest Control Group Design. Random sampling was used for sampling. Data collection techniques included interviews, observation, and documentation. Forty-one fifth-grade students were selected as subjects. Data analysis techniques included the Normality Test, the Homogeneity Test, and the Independent T-test. The results showed that the STAD model was implemented effectively. Based on the results of the independent t-test, it was found that the results obtained at a 2-tailed significance value, namely 0.000 < 0.05, then Ho is rejected and Ha is accepted. In line with the Basis for Decision Making in the Independent Sample Test, if the significance value (2-tailed) < 0.05, then Ho is rejected, and Ha is accepted. The results showed a significant difference between the class that used the STAD model and the class that did not use the STAD model in the ability to calculate multiplication and division.